2009
DOI: 10.1073/pnas.0811685106
|View full text |Cite
|
Sign up to set email alerts
|

G protein-activated inwardly rectifying potassium channels mediate depotentiation of long-term potentiation

Abstract: Excitatory synapses in the brain undergo activity-dependent changes in the strength of synaptic transmission. Such synaptic plasticity as exemplified by long-term potentiation (LTP) is considered a cellular correlate of learning and memory. The presence of G protein-activated inwardly rectifying K ؉ (GIRK) channels near excitatory synapses on dendritic spines suggests their possible involvement in synaptic plasticity. However, whether activitydependent regulation of GIRK channels affects excitatory synaptic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 36 publications
9
109
2
1
Order By: Relevance
“…This provides a means to keep individual glutamatergic synapses modifiable (38,39) and to spare them from inhibition through spillover of GABA. A previous study reported that NMDA receptor activation promotes surface expression of Kir3 channels in hippocampal neurons (40), which was paralleled with an increase in basal Kir3 currents and adenosine A 1 -mediated Kir3 currents (41). However, GABA B mediated Kir3 currents were not altered, in apparent conflict with an earlier report (42) and our own findings.…”
Section: Discussioncontrasting
confidence: 57%
“…This provides a means to keep individual glutamatergic synapses modifiable (38,39) and to spare them from inhibition through spillover of GABA. A previous study reported that NMDA receptor activation promotes surface expression of Kir3 channels in hippocampal neurons (40), which was paralleled with an increase in basal Kir3 currents and adenosine A 1 -mediated Kir3 currents (41). However, GABA B mediated Kir3 currents were not altered, in apparent conflict with an earlier report (42) and our own findings.…”
Section: Discussioncontrasting
confidence: 57%
“…A traditional method to study such plasticity mechanisms is to subject neuronal or synaptic structures to specific activity patterns towards understanding the rules for plasticity in specific components. Assessed through such protocols, distinct synapses show signature profiles of plasticity in terms of activity or cytosolic calcium patterns that result in such plasticity or what other forms of plasticity are concomitant with each other (Abbott and Nelson, 2000;Abbott and Regehr, 2004;Bi and Poo, 1998;Bliss and Collingridge, 1993;Bliss and Lomo, 1973;Chung et al, 2009a;Chung et al, 2009b;Cooper and Bear, 2012;Dittman et al, 2000;Dudek and Bear, 1992;Fortune and Rose, 2001;Frick et al, 2004;Jorntell and Hansel, 2006;Lin et al, 2008;Losonczy et al, 2008;Lujan et al, 2009;Magee and Johnston, 1997;Markram et al, 1997;Johnston, 2007, 2008;Shah et al, 2010;Sjostrom et al, 2008). This implies plasticity profile homeostasis (Anirudhan and Narayanan, 2015;Mukunda and Narayanan, 2017), where synapses and neurons of the same subtype respond similarly to analogous afferent activity, thereby resulting in a subtype-dependent rule for synaptic or neuronal plasticity.…”
Section: Baseline Vs Plasticity Profile Homeostasismentioning
confidence: 99%
“…These studies show that plasticity induction is dependent on influx of calcium through NMDA receptors (Christie et al, 1996;Collingridge and Bliss, 1987;Collingridge et al, 1983;Morris et al, 1986;Mulkey and Malenka, 1992;Nishiyama et al, 2000;Tsien et al, 1996;Wang et al, 2003), voltage-gated calcium channels (Brager and Johnston, 2007;Christie et al, 1996;Christie et al, 1997;Johnston et al, 1992;Moosmang et al, 2005;Nicholson and Kullmann, 2017;Wang et al, 2003), store-operated calcium channels (Baba et al, 2003;Garcia-Alvarez et al, 2015;Majewski and Kuznicki, 2015;Majewski et al, 2016;Prakriya and Lewis, 2015) and receptors on the ER activated by metabotropic receptors on the plasma membrane (Huber et al, 2000;Nishiyama et al, 2000;Verkhratsky, 2002). Additionally, voltage-gated channels and their auxiliary subunits (Anirudhan and Narayanan, 2015;Brager et al, 2013;Chen et al, 2006;Chung et al, 2009a;Chung et al, 2009b;Johnston et al, 2003;Jung et al, 2008;Kim et al, 2007;Lin et al, 2008;Lujan et al, 2009;Malik and Johnston, 2017;Nolan et al, 2004;Sehgal et al, 2013;Shah et al, 2010;Watanabe et al, 2002) have also been shown to critically regulate th...…”
Section: Degeneracy In Calcium Regulation and In The Induction Of Synmentioning
confidence: 99%
See 2 more Smart Citations